Amanah Saham Nasional Berhad (ASNB) Kangar / Siti Hawa Mohd Zamri - Mohd Zamri, Siti Hawa (Universiti teknologi MARA,Perlis, 2023)
This report is about my internship program with Amanah Saham Nasional Berhad (ASNB) Kangar. I have addressed every key component of the investing company that I observed and perceived during my internship program in this exhaustive report. During my industrial training, I mostly worked in the Branch Management & Supervision Department, which was responsible for assisting the branch in meeting the needs of the unit holders. However, the job scope is varied and I did learn to manage and process most of the major services that ASNB offered. As the fundamental purpose of an internship is to learn by working in a practical environment and applying the knowledge learned during studies in a real-world scenario to solve problems using the knowledge and skills gained during the academic process. The purpose is to use the material provided by the company to learn and gain experience in the ASNB working environment. This internship report covers a wide range of important subjects, the vast majority of which are related to the company's operations and finances. All of the policies, processes, practices, and procedures that I went through and learned during my internship program are included at the end of the learning and experience section. This research also examines The Determinants of Saving Behaviors in Malaysia.